CONVERGENCE AND DIVERGENCE BETWEEN ECOCENTRISM AND SENTIENTISM CONCERNING NET VALUE - MIKKELSON, GREGORY (Les ateliers de l'éthique / The Ethics Forum, 2018)
Animal and environmental ethics should converge on the following three value judgments: natural ecosystems generally involve more good than harm; predation in nature tends to yield positive net benefits; and, at least on a global scale, livestock farming is destroying more value than it is creating. But the ecocentric criteria of environmental ethics and the sentientist criteria of animal ethics may have divergent implications for capitalism’s main effect on the world: the collapse of wild nature due to explosive growth in the human economy. Sentientism risks counting this effect as a net gain, whereas ecocentrism surely rates it a massive net loss. While supporting the above claims, I show how they fit into a larger argument in favour of the broader, ecocentric value theory of environmental ethics and against the narrower, sentientist axiology of animal ethics.